A Lexical Analysis of בָּרֹד and מֵֽהִתְיַצֵּ֖ב of In Zechariah 6:3-5 - Philip Suciadi Chia; Juanda Juanda (Jurnal Didaskalia, 2020)
In the Zechariah, there are various visions and prophecies that are so difficult to be understood today. And this can be biased if every Bible’s learner interprets it as he pleases. In this research, which uses the Lexical Analysis approach, will discuss about the meaning of the words בָּרֹד and מֵֽהִתְיַצֵּ֖ב of In Zechariah 6:3-5. With in-depth observation and also making language comparisons, it can be concluded that: בָּרֹדin Zechariah 6:3 should be translated as dappled, a literal or concrete definition. Old Testament does not give any specific color with regard to the dappled. However, it seems that the color of horses in Zechariah 6:1-8 has a function to distinguish one chariot from the other chariots. יצבin Zechariah 6:5 should be interpreted in the sense of readiness to serve God, a metaphorical extension of the concrete definition, ‘to stand’. The four spirits are going forth after serving the Lord of all the earth in the heavens. It implies that the four spirits are belonged to God. In the heavens, they are serving God and when going to the earth, they carry God’s mission.